Most přes potok Hluchová - stavebně technologický projekt - Trochta, Ondřej (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Diplomová práce se zabývá tvorbou stavebně technologického projektu mostu SO210 přes potok Hluchová na silnici I/11. Most je navržen jako železobetonový, dodatečně předpjatý o délce 70m. Práce byla zpracována v rozsahu zadání DP.

The diploma thesis deals with the construction of the technical project of the SO210 bridge over the stream Hluchová on the I / 11 road. The bridge is designed as reinforced concrete, additionally prestessed with a length of 70m. The thesis was processed within the scope of DP assignment.
The bridge over the creek Hluchova - building and technological project
Keywords: Předpjatý beton; mostní konstrukce; most; piloty; štětovnice; pevná skruž; mostní pilíř; mostní opěry; svodidla; potok; BOZP; Prestressed concrete; bridge construction; bridge; piles; fixed bridge; bridge pillar; bridge supports; barriers; stream; BOZP